TOGA: Tanaman Obat Keluarga Sebagai Upaya Menjaga Kesehatan Masyarakat Desa Padang Lua di Masa Pandemi - Pernantah, Piki Setri; Pertiwi, Adelia; Aminullah, Almanda Fajar; S, Erfa Julia; Davista, Halim; Astuti, Indria; Silvia, Leni; Hamdani, M. Luthfi; Rahmadhani, Rahmi; Syafanah, Sarah Azkha; Prahasiwi, Syifa Wahyuni (Journal of Community Engagement Research for Sustainability, 2022)
This service is carried out in the situation of communities that are still hit by the COVID-19 pandemic and make health a top priority to keep life running in a new normal. The current situation makes health an important factor so that people avoid this dangerous virus. The phenomenon in the field can be seen there are still many people who are struggling and afraid to go for treatment. Therefore, we hold devotional activities that can be an alternative for the community in Nagari Padang Lua to utilize family medicinal plants (TOGA) as a supporter of public health. Our method is to strengthen understanding of the importance of family medicinal plants and revive long-lost Family Medicinal Plants (TOGA). We cooperate with the PKK (Family Welfare Empowerment) team in Nagari Padang Lua as a trusted agency so that it can attract the interest of the surrounding community to participate in this activity. The result of this service is expected so that the community has no difficulty in obtaining medicines and can switch back to herbal medicine to maintain public health in times of pandemics. By maintaining health, we hope that the covid-19 virus can be lost on our beloved earth.